2019
DOI: 10.1111/jth.14347
|View full text |Cite
|
Sign up to set email alerts
|

Preventing arteriovenous shunt failure in hemodialysis patients: a population‐based cohort study

Abstract: Uncertainty remains about antiplatelets for vascular access patency in hemodialysis patients. 95 971 people under hemodialysis were followed in a claims database in Taiwan. Aspirin reduced vascular access failure rate and did not increase major bleeding rate. Clopidogrel, Aggrenox, and warfarin might increase major bleeding rate. Summary BackgroundDialysis adequacy is a major determinant of survival for patients with end‐stage renal disease. Good vascular access is essential to achieve adequate dialysis. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…A retrospective evaluation of over 90,000 ESRD patients in the Taiwan National Health Insurance Program were studied to estimate the efficacy of thrombosis prevention and risk of bleeding with different antiplatelet agents and oral anticoagulants. Anti-platelet agents, but not warfarin, reduced the risk of vascular access thrombosis rate, but there was an increased risk of bleeding with clopidogrel and aspirin-dipyridamole [28]. An analysis of 24,847 hemodialysis patients who had vascular access placement from the Society for Vascular Surgery Vascular Quality Initiative showed that primary patency of AVG but not AVF was improved in patients receiving antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective evaluation of over 90,000 ESRD patients in the Taiwan National Health Insurance Program were studied to estimate the efficacy of thrombosis prevention and risk of bleeding with different antiplatelet agents and oral anticoagulants. Anti-platelet agents, but not warfarin, reduced the risk of vascular access thrombosis rate, but there was an increased risk of bleeding with clopidogrel and aspirin-dipyridamole [28]. An analysis of 24,847 hemodialysis patients who had vascular access placement from the Society for Vascular Surgery Vascular Quality Initiative showed that primary patency of AVG but not AVF was improved in patients receiving antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One person-quarter (PQ) was used as an analytical unit. We used PQs because medications for chronic illnesses were refilled with a maximum duration of 3 months per the Taiwan NHI reimbursement policy ( 16 , 18 ). Medications and covariates were assessed for each PQ, and PQs exposed to DOACs with or without statins were identified.…”
Section: Methodsmentioning
confidence: 99%
“…From the DOPPS observational study, use of warfarin was associated with worse primary graft patency (RR 1.33; P = 0.037) 19 . A retrospective cohort study from Taiwan showed no benefit from warfarin use at reducing need for thrombectomy or percutaneous angioplasty, but use of warfarin significantly increased risk of ICH 20 . A 2002 RCT of 107 ESKD patients with PTFE grafts in Ontario, Canada, randomized patients to low intensity warfarin (INR goal 1.5–1.9) or placebo and showed no significant difference in graft survival but did show significantly increased major bleeding in the treatment arm 21 .…”
Section: Introductionmentioning
confidence: 99%
“…19 A retrospective cohort study from Taiwan showed no benefit from warfarin use at reducing need for thrombectomy or percutaneous angioplasty, but use of warfarin significantly increased risk of ICH. 20 A 2002 RCT of 107 ESKD patients with PTFE grafts in Ontario, Canada, randomized patients to low intensity warfarin (INR goal 1.5-1.9) or placebo and showed no significant difference in graft survival but did show significantly increased major bleeding in the treatment arm. 21 The effect of direct oral anticoagulants on VAT is not known currently and is an area of ongoing research (NCT04489849).…”
mentioning
confidence: 99%